Marketing Mix Factors that Influence Visitors Choose Aeon Mall as a Shopping Tourism Destination - Naftali, Cathy; Nursiana, Adinoto; Brahmantyo, Himawan (Jurnal Penelitian Pariwisata, 2017)
Aeon mall is company from Japan, and joint venture with Sinarmas Land for PT.AMSL Indonesia. Aeon mall grand opening in BSD, Tangerang 30 May 2015, after two years from the opening Aeon Mall has already many visitors from area in Jabodetabek. Marketing mix approach is used from Morrison (2002) product, price, place, promotion, people, packaging and programming, also partnership. The aim of this study was to determine the effect of marketing mix based on Morrison theories to visitor decision of visiting Aeon Mall. This research used descriptive method approach. The population in this study is Aeon Mall visitors. The respondent was chosen by random sampling. The numbers of respondents are 218 people. The data was collected by distributing questionnaires. The analysis technique used validity and reliability, frequencies, mean, the classical assumption test, t-test, f-test, regression analysis, hypothesis test and coefficient of determination by using SPSS for windows 20.0. The study found that there was a positive and significant impact of product, promotion, and partnership to visitor’s decision of visiting Aeon Mall. But there wasn’t a positive and significant effect of price, place, people, packaging and programing to the visitor’s decision of visiting Aeon Mall.